State regulation of interregional differentiation in Kazakhstan (Journal of Economic Research & Business Administration, 2020)
Excessive differentiation at the level of socio-economic development of the regions leads to thedisintegration of a single socio-economic space and the emergence of territorial imbalances in economicand social structures, which entails a decrease in the functioning efficiency of not only regional, butalso the national economy as a whole. Since territorial socio-economic imbalance is accompanied by anumber of negative consequences, their overcoming is defined as an important direction of state policyin most countries and regions of the world.Therefore, the aim of the article is to study different ways to minimize the negative effects of interregionaldifferentiation, which exacerbates social tension and impedes balanced economic development,by identifying factors affecting the occurrence of socio-economic imbalances.Based on the results of the study, specific recommendations were formulated to eliminate the identifiednegative consequences of interregional differentiation in terms of GRP per capita on the developmentof regions, the influence of investment activity on distinction in their development is investigated,and the role of financial resources in smoothing interregional differentiation is justified.The theoretical and methodological basis of this study is the work of domestic and foreign scientistson the theory and practice of inequality in the socio-economic development of regions. The study usedmethods of comparative economic analysis, expert assessment methodology and a systematic approach.The article substantiates the thesis that the reduction of differentiation between the regions of Kazakhstanwill allow the socio-economic system of the regions to function efficiently, improve the qualityof life of the population, and reduce social tension.